Effects of thickness and fiber volume fraction variations on strain field inhomogeneity. (February 2015) - Jensen, Eric M.; Leonhardt, David A.; Fertig, Ray S.
Abstract: In this study, variations in thickness and fiber volume fraction are investigated as causes of elastic strain inhomogeneity in composite laminates under an applied transverse load. Standard carbon/epoxy tensile specimens were fabricated from unidirectional pre-impregnated material using two different manufacturing techniques that produced two different levels of surface roughness. Fiber volume fraction variation was computed by analyzing optical micrographs of the samples. During loading and unloading of the samples two-dimensional surface strain fields were measured on the specimen using digital image correlation. It was shown that in both cases the strain in the specimen is not uniform, as is generally assumed. Using finite element simulations the effects of fiber volume fraction variation and thickness variation were modeled individually and in combination. The simulations agree well with the experimental results and suggest that thickness variations are the dominant mechanisms involved in this elastic strain inhomogeneity.